Pembuatan Aplikasi Sistem Informasi Dayah Istiqamatuddin Raudhatul Mu’arrif Berbasis Web - sanusi sanusi; Juniana Husna; Ryan Setiawan; Rizka Dara Fonna (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2023)
Dayah Istiqamatuddin Raudhatul Mu'arrif is a traditional Islamic school/ dayah salafi located at Hamlet Alue Seuneuhi, Gampong Neuheun, Grand Mosque districts, Aceh Besar. Administrative process and management of students and educators data of the Islamic school of Istiqamatuddin Raudhatul Mu'arrif still use the manual method by relying on the master book. The use of computers for dayah administration is still not maximized, depending only on Microsoft Word and Microsoft Excel applications. Therefore, when the data is needed cannot be obtained in a fast time. The system was built to help recap student and teacher data more efficiently to minimize errors in report generation. It is designed and built using the Laravel framework so that the structure of the codes becomes neater and safer from external attacks. In addition, the MySQL query language is used for database access and management. The results obtained are an information system application that can display the complete profile of Dayah Istiqamatuddin Raudhatul Mu'arrif and monitor the administration management. Furthermore, it can be printed and downloaded by the administrative manager